The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/su12072866
|View full text |Cite
|
Sign up to set email alerts
|

Hematite/Graphitic Carbon Nitride Nanofilm for Fenton and Photocatalytic Oxidation of Methylene Blue

Abstract: Hematite (α-Fe2O3)/graphitic carbon nitride (g-C3N4) nanofilm catalysts were synthesized on fluorine-doped tin oxide glass by hydrothermal and chemical vapor deposition. Scanning electron microscopy, energy-dispersive spectroscopy, X-ray diffraction, and X-ray photoelectron spectroscopy analyses of the synthesized catalyst showed that the nanoparticles of g-C3N4 were successfully deposited on α-Fe2O3 nanofilm. The methylene blue degradation efficiency of the α-Fe2O3/g-C3N4 composite catalyst was 2.6 times grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…MO degradation was significantly suppressed when BQ was utilized as a scavenger. Thus, the results of the trapping experiments clearly demonstrate that the hydroxyl radical (•OH) and hole (h + ) play a minor role in the photocatalytic removal of MO, whereas, O2 •− is the primary ROS that further degrades the MO over the g-C3N4/α-Fe2O3 nanocomposite, which is in good agreement with recent studies [44][45][46][47].…”
Section: Photocatalytic Mo Degradation Mechanismsupporting
confidence: 90%
“…MO degradation was significantly suppressed when BQ was utilized as a scavenger. Thus, the results of the trapping experiments clearly demonstrate that the hydroxyl radical (•OH) and hole (h + ) play a minor role in the photocatalytic removal of MO, whereas, O2 •− is the primary ROS that further degrades the MO over the g-C3N4/α-Fe2O3 nanocomposite, which is in good agreement with recent studies [44][45][46][47].…”
Section: Photocatalytic Mo Degradation Mechanismsupporting
confidence: 90%
“…[ 30,31 ] It also catalyzes Fenton and photo‐Fenton reactions with UV‐light irradiation and H 2 O 2 , producing more ROS to attack pollutants in water. [ 32 ] These characteristics make it an appealing material for the fabrication of visible light‐powered micro/nanorobots for water remediation. However, hematite photocatalytic applications are limited by its high electron–hole recombination rate and low electron mobility.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that all prepared iron oxides with and without surfactants were formed in spherical α-Fe 2 O 3 with a diameter range of 15-205 nm based on the surfactant sort and concentration. As well many hematite composites were fabricated using a hydrothermal route, such as activated carbon/α-Fe 2 O 3 (Ermanda et al 2021), Co-doped α-α-Fe 2 O 3 (Cai et al 2021), α-Fe 2 O 3 /g-C 3 N 4 (Lee and Park 2020), and chitosan-coated-α-Fe 2 O 3 (Badry et al 2021).…”
Section: Hydrothermalmentioning
confidence: 99%